Problems of canistherapy as the new method in practical social work - Садрицька, С. В. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2021)
The history of coexistence and mutual assistance between man and dog is almost 40 thousand years old, but as a direction of therapy, "canistherapy" began to develop only in the midtwentieth century. This has been due to the large body of scientific research that has shown the therapeutic effect of animals, including dogs, on the human condition. The aim of the article is to try to conceptualize this new social phenomenon not only as a socially significant way of human-animal interaction, but also as the latest method of practical social work. According to the author, canistherapy is one of the effective technologies of social rehabilitation, as it helps to restore broken or lost social ties and social functions. Examples of the use of this method in geriatric institutions, clinics, hospitals, rehabilitation centers are given. Considering the research of the method of canistherapy for various diseases and disorders, the author concludes on the possibilities of using canine therapy in practical social work with such groups of clients as the elderly, people with disabilities, "difficult teenagers", people with various forms of addiction, children with disability and cerebral palsy, Down syndrome, autism. The possibilities of the method in working with people who have vision problems deserve a separate analysis. The main components of canistherapy and its forms such as meeting-communication with a dog are considered in the article; training with a dog; systemic therapy. The main components of canistherapy and its form are considered in the article. According to the author, this area is promising and is developing quite actively in Ukraine, but still has no official recognition and support from the state. Based on the opinion of experts, the article identifies the main problems that hinder the development of this method. It is emphasized that in Ukraine there is no system of training of specialist canine therapists, in order to obtain a diploma or certificate, both specialists and dogs must go abroad. Among the problems of method development, the author emphasizes the lack of organizational mechanisms that would combine the efforts of psychologists, cynologists, social workers with the needs of clients. Without the support of the state, the author is sure, the method will be developed only through volunteers and on a commercial basis, which significantly limits its use in the field of social rehabilitation and makes it impossible to ensure the quality of such services. Key